Prophylactic intravenous paracetamol for prevention of shivering after general anesthesia in elective cesarean section - Ahmadreza S Gholami; Mehdi Hadavi (Wolters Kluwer Medknow Publications, 2016)
Background: Postoperative shivering is an important common complication after general anesthesia. This may lead to dissatisfaction and a sense of discomfort, especially in parturients undergoing cesarean section. In addition to warming, many drugs have been investigated for prevention of shivering. The aim of this study was to evaluate the efficacy of intravenous paracetamol for prevention of shivering after general anesthesia in cesarean section. Materials and Methods: In this prospective randomized double-blind controlled clinical trial, 110 pregnant women, physical Status I or II, based on the classification of American Society of Anesthesiologists (ASA), aged 18-40 years, who were scheduled for elective cesarean section under general anesthesia were included in the study. They were randomly divided into two groups of 55 each. One group received 100 ml normal saline, and another group received 1 g of paracetamol in 100 ml normal saline intravenously, 15 min after the delivery of the baby. The anesthesia technique was similar in both the groups. Tympanic membrane temperature was measured before and after the induction of anesthesia and every 15 min till the end of recovery from anesthesia. Postanesthetic shivering was graded on a scale of 0 to 4; if the score was more than 2, it was treated with 25 mg pethedine. Vital signs and side effects were recorded during the surgery and recovery period. Results: There were no significant differences between the two groups regarding age, weight, height, and duration of surgery (P > 0.05). Shivering was seen in 5 parturients (9.1%) in paracetamol group (group A) and 28 parturients (50.9%) in the saline group (group N). On a scale of 0 to 4, shivering was of lower intensity in paracetamol group compared to the saline group (P < 0.05). There was a fall in core temperature in both the groups after induction of anesthesia, which was statistically similar (P > 0.05). There was no difference in the incidence of hypotension, nausea, and vomiting among the two groups (P > 0.05). Conclusion: The prophylactic use of intravenous paracetamol during surgery is effective for the prevention of postoperative shivering.